THE CRIMINAL POLICY FORMULATION AT LAW ENFORCEMENT PENAL FORESTRY - Wirya, Astan (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The criminal policy formulation at law enforcement penal forestry on this thesis is about problem and what criminal formulation policy in tackling a forestry criminal act and what competence and effort to eliminate forestry destruction institution (LP3H) based on ordinance number 18 years 2013, regarding prevention, and elimination of forestry impairment, this research is about normative and doctrinal law and supporting by law element such premier, secondary and tarsier law. Approach system in this thesis using statue approach, conceptual approach, historical approach, meanwhile an analyze research basic law interpretation with deductive and inductive concept as the explanation, logic interpretation and systematic. The criminal policy formulation at law enforcement penal forestry has been direction through criminal law regulation (KUHP), an ordinance number 5 years 1990 regarding ecosystem resource and conservation, an ordinance number 41 years 1999 regarding forestry and ordinance number 18 years 2013, regarding prevention and elimination of forestry impairment, an criminal law enforcement policy on the ordinance number 18 year 2013 has been divide a type of criminal case, criminal responsibilities and criminality system with minimum particularly up to maximum which criminal responsibilities distinguish into personal, person to person around forestry, corporate, and government authorities. An ordinance number 18 years 2013 regarding the P3H, dedicate and declare tackling a forestry criminal act and what authority and effort to eliminate forestry destruction institution (LP3H), those institution under president supervise, institution element including Forest Ministry, Indonesian Police, Public Persecutor and others, institution structure lead by a chairman helping by some deputy such as prevention deputy broad, measures, law, and cooperation, internal supervise and community complain deputy, P3H institution has right and function for forest destruction prevention, by input the local community participate, fill up a basic resource, campaign of forest destruction. a right of law measures, investigation, pursuit, up to court interrogation. Institution P3H also has right and function to coordinate supervise a criminal forest lawsuit act.Key word : Criminal policy, formulation law and penal forestry.